Determinants of Drug Adherence on Grade Two and Three Patients with Hypertension - Riza Fikriana; Shrimarti Rukmini Devy; Ahsan Ahsan; Al Afik (Universitas Airlangga, 2019)
Background: Compliance for taking medication to become an important thing for a patient with hypertension. Compliance is needed to control blood pressure and prevent complication. The purpose of this study was to analyse the factors that influence patients adherence to taking medicine.Method: The study design was observational analytic using a cross-sectional approach. Samples were 225 patients with hypertension class 2 and 3, in Malang district, Indonesia. The sampling technique was done by using a multistage random sampling technique. The research instrument was in the form of a questionnaire. Data analysis was performed using the Pearson test and linear regression.Results: The results showed that patients adherence in taking medicine was 32.9% for the low category, 51.1% in the medium category and 16% in the good category. Factors influencing the adherence were ages (p-value: 0.002), turning to religion (p-value: 0.011), gender (p-value: 0.016) and suppressing competition activities (p-value: 0.063).Discussion: Demographic characteristics and focused emotional mastery influence taking the medication in patients with grade 2 and grade 3 hypertension. Strengthening coping strategies with transporting to coping emotions becomes very important to discuss in patients with grade 2 and grade 3 hypertension, so that adherence to hypertension is needed will be able to control blood pressure and prevent complications.